1997
DOI: 10.1525/maq.1997.11.2.183
|View full text |Cite
|
Sign up to set email alerts
|

Sociocultural Aspects of Tuberculosis Control in Ethiopia

Abstract: This article examines ethnomedical knowledge and practices related to tuberculosis conceptualization and management in a rural southern Ethiopian community. An adult health-status survey, administered to 217 adults selected through quota sampling procedures, investigated prevailing nosological structures. Additionally, disease-enhancing behaviors were identified through qualitative-research methods. The findings show that while symptomatological concepts coincide with biomedicine, the local etiological model p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
2
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 32 publications
2
20
2
2
Order By: Relevance
“…Qualitative findings provided insight that many patients were unsure how to combine the variety of TB perceptions available. Previous studies have shown the importance of perceptions on health care seeking behaviour [2832] and have stressed the importance of cultural-sensitive sensitisation programmes [7, 8, 33]. We propose interactive awareness programmes that acknowledge and appropriately address the variety of local perceptions to enhance early case-finding and reduce hospital delay.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative findings provided insight that many patients were unsure how to combine the variety of TB perceptions available. Previous studies have shown the importance of perceptions on health care seeking behaviour [2832] and have stressed the importance of cultural-sensitive sensitisation programmes [7, 8, 33]. We propose interactive awareness programmes that acknowledge and appropriately address the variety of local perceptions to enhance early case-finding and reduce hospital delay.…”
Section: Discussionmentioning
confidence: 99%
“…However, these social expectations and associated power structures have not been reported by previous socio-anthropological TB studies. 5,6,11,25 This fi nding highlights the need for culturally sensitive TB health education in which traditional/religious perceptions and practices are not neglected, but identifi ed as part of the cultural context. Similarly, embedding the medical perspective in the socio-cultural context could advance communications between health care providers and patients.…”
Section: Public Health Action Treatment Adherence In Gabon 331mentioning
confidence: 95%
“…Felt or feared stigma occasionally led to fear of disclosure and self-exclusion from health care services. 25 One study described how the chronic nature of TB aggravated stigma. 7 Interestingly, during focus group discussions and interviews, TB stigma was often denied because of the curable nature of the disease.…”
Section: Public Health Action Treatment Adherence In Gabon 331mentioning
confidence: 99%
See 1 more Smart Citation
“…que cobra sentido las prácticas y conocimientos locales. De hecho, no aparece estudio social previo ni referencias bibliográficas a otros autores que, desde otras disciplinas, han estudiado los factores socioculturales que han influido en el control de la TBC (Vecchiato, 1997). Tal y como se deduce de estas publicaciones, los proyectos a pesar de sus equívocos títulos son, en realidad, una manera de 'captar' agentes para la puesta en marcha de la terapia farmacológica antituberculosa.…”
Section: El Análisis Científico De Lo Tradicionalunclassified